Pattern of Female Genital Tract Malignancies at Delta State University Teaching Hospital, Oghara, Nigeria - esemuede, omonigho; Okhionkpamwonyi , Osamudia; Abedi, Harrison (African Journal of Tropical Medicine and Biomedical Research, 2025)
Introduction: Cancers of the female genital tract contribute significantly to cancer-related morbidity and mortality globally. The pattern and distribution of these malignancies vary from region to regions. The objective of this study was to determine the incidence, pattern of presentation and distribution of the different types of genital tract malignancies in Delta State. Materials and Methods: It was a cross sectional descriptive study of gynaecological malignancies managed at the Delta State University Teaching Hospital, Oghara from January 2013 to December 2015. Case notes of all patients seen with gynaecological malignancies confirmed histo-pathologically during the studied period were retrieved. The required information was extracted from the case notes. Results: A total of 3964 patients were seen at the gynaecological clinics during the period and 137 of these patients had gynaecological malignancies, with incidence of 3.5% of total gynaecological patients. Cervical cancer accounted for 68.42% of the cases. This was followed by ovarian cancer, comprising 15.79% and endometrial cancer, 12.78%. Vulvar cancer and choriocarcinoma were least occurring, accounting for 1.5% each. The mean age of all patients with genital tract malignancies was 51.26 ± 13.2years. The mean ages of patients with cervical, ovarian and endometrial cancers were 42.70 ± 3.15, 61.52 ± 6.82 and 58.76±5.57years respectively. The mean parity was 5.62 ±1.74. Conclusion: Cervical cancer was the most common female genital malignancy and a higher proportion of the patients were grandmultiparous women with postcoital bleeding being the most common clinical presentation.